Prototype-Based Flood Detection Device Ultrasonic Sensor HC-SR04 And Using Lora SX1278 Case Study Gelam Sidoarjo - Exsavator Dwiryanto Putra; Indah Sulistiyowati; Shazana Dhiya Ayuni (Merdeka Malang University, 2024)
The prototype device is a flood detection tool based on an ultrasonic sensor HC-SR04 and using a LoRa SX1278 module. The device is designed for use in a flood case study in Gelam, Sidoarjo. The ultrasonic sensor measures the water level around the device, while the LoRa module transmits the water level data to a receiving device. With this device, it is expected that the surrounding community can monitor the water level in the area, thereby predicting the risk of floods and taking necessary preventive measures. The device can also help authorities make the right decisions in dealing with flood situations. However, it should be noted that this is a prototype device and still needs to be tested more widely to determine its accuracy in monitoring water levels and the reliability of the LoRa module in transmitting data.